Sixty-seventh annual report and documents of the New York Institute for the Instruction of the Deaf and Dumb to the legislature of the state of New York, for the year 1885. - New York Institute for the Instruction of the Deaf and Dumb (New York : New York Institute for the Instruction of the Deaf and Dumb, 1886)
Jaaroverzicht van dit instituut voor doven en geestelijk gehandicapten.